The role of UNICEF in addressing child marriage issues in Indonesia - Kirana, Priscilla Dewi; Nisak, Qudwatin (Universitas Islam Negeri Ar-Raniry, 2022)
Early marriage completely undermines children's human rights. Previous studies have shown that child marriage is inextricably linked to various adverse impacts, from violated children's rights to obtain education and access to health services to intergenerational poverty. Indonesia is in the 8th highest rate of early childhood marriages internationally and is ranked 2nd in ASEAN. This phenomenon has put Indonesia in the spotlight of The United Nations Children's Fund (UNICEF). This research, which relies on interviews and observations from various related documents, aims to analyze the role implemented by UNICEF in tackling the problem of child marriage in Indonesia for the 2017-2020 period. The theories and concepts applied are the theory of international organizations, role theory, and the concept of child marriage. Furthermore, the author used data analysis model according to Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing/verification. The final results of this study reveal that UNICEF is playing their role in providing information on child marriage, advocating for policies, introducing innovations to address challenges, and supplying technical assistance to improve the quality of social services. In addition, UNICEF partners with governments to ensure that resources are employed to meet the needs of children, create spaces for children to be involved in the development process and strengthen collaboration for child's interests.Keywords: UNICEF; child marriage; international organizations; role theory.